METHODS OF SOLVING PROBLEMS IN OLYMPIAD ISSUES IN MATHEMATICS - Nadir Jonadilugli Quljonov; Humoyun Shovxidinugli Abdigaffaforov (Web of Journals Publishing, 2023)
Today, in the continuous education system, the use of various methods and experiences is of great importance in improving the quality and efficiency of education. This article describes the importance of "Methods of solving Olympic problems by using functions".
Keywords: Function, concept of symmetry, quadratic equation, analytical methods of teaching, teaching methodology.